Polyethylene composite film and two-way stretching process thereof
By combining zinc oxide and hindered amine light stabilizer on graphene oxide nanosheets in polyethylene films and combining silica aerogel powder, the electrostatic and ultraviolet aging problems of polyethylene films are solved, and the anti-static and ultraviolet properties are improved, and the mechanical and conductive properties are enhanced.
Patent Information
- Application Number
- CN202510586683.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-08
- Publication Date
- 2025-08-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polyethylene films are prone to aging due to static electricity accumulation and ultraviolet rays when used outdoors, resulting in a decrease in transparency and mechanical properties.
By combining zinc oxide with hindered amine light stabilizer on graphene oxide nanosheets, combining silica aerogel powder, the anti-static and ultraviolet properties are improved, and a polyethylene composite film is prepared through a bidirectional stretching process.
It improves the anti-static and ultraviolet properties of polyethylene composite films, reduces dust accumulation, enhances mechanical and conductive properties, and extends service life.
Smart Images

Figure BDA0005391910680000101 
Figure BDA0005391910680000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyethylene materials, in particular to a polyethylene composite film and a biaxial stretching process thereof. Background Art
[0002] Polyethylene film, with its excellent chemical stability, heat-sealability, and low price, is one of the most widely used materials for agricultural cover cropping and industrial production. Polyethylene film can be formed using methods including blow molding, cast film, and biaxial stretching. Biaxial stretching is easy to control, and film products offer high transparency and oxidation resistance.
[0003] However, the surface of highly transparent polyethylene film is prone to accumulate static electricity due to its own high resistivity, causing dust or liquid in the air to accumulate on the surface of the polyethylene film, which will cause the transparency of the polyethylene film to decrease and affect its use.
[0004] Chinese invention patent application publication number CN113105688A discloses a conductive packaging film, a preparation method, and a conductive packaging bag. By arranging a substrate layer and a conductive layer, a conductive layer is formed from conductive materials such as graphene and carbon nanotubes, and is composited with a substrate layer formed from polymer materials such as polyethylene resin to obtain a film with good conductive properties. However, the film in this solution has low resistance to ultraviolet oxidation and is easily aged when exposed to ultraviolet rays outdoors for a long time, resulting in a decrease in mechanical properties and light transmittance.
[0005] Chinese invention patent application publication number CN116589769A discloses a PE film with UV shielding function and its preparation method. By incorporating a UV shielding finishing agent into the gaps in lignin, the large amount of UV shielding finishing agent escaping from the polyethylene matrix is reduced, solving the problem of film powdering and performance degradation. However, this solution has poor electrical conductivity and is prone to dust accumulation on the film surface due to static electricity, affecting the film's light transmittance. Summary of the Invention
[0006] The purpose of the present invention is to improve the antistatic and anti-ultraviolet properties of a polyethylene film and to provide a polyethylene composite film and a biaxial stretching process thereof.
[0007] The present invention combines zinc oxide and hindered amine light stabilizers to synergistically improve the anti-ultraviolet performance of the polyethylene composite film, and combines zinc oxide on graphene oxide nanosheets to improve the antistatic performance of the polyethylene composite film, while reducing the influence of fillers on the mechanical properties of the polyethylene composite film.
[0008] The purpose of the present invention can be achieved through the following technical solutions:
[0009] A polyethylene composite film, comprising the following components in parts by mass:
[0010] 4-5 parts of graphene oxide / silicon dioxide aerogel powder, 30-40 parts of linear low-density polyethylene, 100-120 parts of high-density polyethylene, 40-60 parts of low-density polyethylene, 0.5-0.8 parts of dispersant and 0.3-0.5 parts of antioxidant.
[0011] The graphene oxide / silicon dioxide aerogel powder is prepared by mixing loaded graphene oxide and silicon dioxide aerogel and then subjecting them to hydrophobic modification.
[0012] The loaded graphene oxide is prepared by loading zinc oxide / carbon / graphene oxide with a hindered amine light stabilizer.
[0013] Furthermore, the antioxidant is one of antioxidant 168, antioxidant 1076 and antioxidant 330; the dispersant is one of polyethylene wax and methyl stearate; and the hindered amine light stabilizer is HALS 770.
[0014] Furthermore, the graphene oxide / silicon dioxide aerogel powder is specifically prepared by the following steps:
[0015] In a reactor, ethyl orthosilicate and a 70 wt% ethanol aqueous solution are stirred and mixed for 8-10 hours, and the pH value is adjusted to neutral with dilute ammonia water. The loaded graphene oxide is ultrasonically dispersed in ethanol, added to the reactor, and ultrasonically treated for 30-40 minutes to form a gel. After aging, ageing, and solvent replacement, the gel is immersed in a mixed solution of trimethylchlorosilane and n-hexane for 40-48 hours to obtain a hydrophobically modified gel. The hydrophobically modified gel is dried at 50-60° C. for 1-2 hours, and then at 140-150° C. for 2-3 hours, and then crushed through a 300-mesh sieve to obtain graphene oxide / silica aerogel powder.
[0016] Furthermore, the usage ratio of ethyl orthosilicate, ethanol aqueous solution, loaded graphene oxide and ethanol is 10-15 g:80-100 mL:3-4 g:150-200 mL; and the volume ratio of trimethylchlorosilane and n-hexane is 1:9.
[0017] Furthermore, the supported graphene oxide is specifically prepared by the following steps:
[0018] In a reaction kettle, zinc oxide / carbon / graphene oxide is ultrasonically dispersed in ethanol, a hindered amine light stabilizer is added, and the mixture is stirred and dissolved, and then the solvent is removed by rotary evaporation to obtain loaded graphene oxide.
[0019] Furthermore, the usage ratio of zinc oxide / carbon / graphene oxide, ethanol and hindered amine light stabilizer is 2-3 g:50-60 mL:1-2 g.
[0020] Furthermore, zinc oxide / carbon / graphene oxide is prepared by the following steps:
[0021] The porous zinc skeleton / graphene oxide was heated to 600-700° C. under nitrogen protection in a tubular furnace and carbonized for 2-3 h to obtain zinc oxide / carbon / graphene oxide.
[0022] Furthermore, the porous zinc skeleton / graphene oxide is prepared by the following steps:
[0023] Zinc nitrate hexahydrate is dissolved in DMF in a reactor, and then graphene oxide nanosheets and 3-3.5 mL of polyvinyl pyrrolidone are added, stirred and ultrasonically treated for 30-40 minutes, and 2,5-dihydroxyterephthalic acid DMF solution is added to the reactor. After stirring and mixing for 2-3 hours, the temperature is raised to 110-120° C. and the reaction is carried out for 1-2 hours. After cooling, the precipitate is collected by centrifugation, washed with ethanol and deionized water, and vacuum dried at 70-80° C. to obtain a porous zinc skeleton / graphene oxide.
[0024] Furthermore, the usage ratio of zinc nitrate hexahydrate, DMF, graphene oxide nanosheets, polyvinyl pyrrolidone and 2,5-dihydroxyterephthalic acid DMF solution is 3.5-5 g: 200-250 mL: 2-3 g: 200-250 mL.
[0025] Furthermore, the 2,5-dihydroxyterephthalic acid DMF solution is prepared by mixing 2,5-dihydroxyterephthalic acid and DMF in a ratio of 4-6 g: 200-250 mL.
[0026] A biaxial stretching process for a polyethylene composite film comprises the following steps:
[0027] Graphene oxide / silica aerogel powder and linear low-density polyethylene are melt-blended and extruded in a twin-screw extruder to obtain reinforced low-density polyethylene, and then the reinforced low-density polyethylene, high-density polyethylene, low-density polyethylene, a dispersant and an antioxidant are melt-mixed and extruded into granules in a twin-screw extruder to obtain pellets. The mixing temperature of the twin-screw extruder is 220-245°C and the rotation speed is 200-250rpm. The extruded pellets are molded into sheets at a molding temperature of 190-200°C. The sheets are simultaneously biaxially stretched in a biaxial stretcher at a strain rate of 3-4 / s and at 125-125°C to obtain a polyethylene composite film.
[0028] Beneficial effects of the present invention:
[0029] 1. The polyethylene composite film prepared by the present invention compounds zinc oxide and hindered amine light stabilizers to synergistically improve the anti-ultraviolet performance of the polyethylene composite film. By compounding zinc oxide on graphene oxide nanosheets, the antistatic performance of the polyethylene composite film is improved, and the influence of the filler on the mechanical properties of the polyethylene composite film is reduced. The obtained polyethylene composite film has good mechanical properties and resistance to ultraviolet aging. At the same time, it has low surface resistance and is not prone to dust accumulation on the surface of the film due to static electricity, resulting in performance degradation.
[0030] 2. The polyethylene composite film prepared by the present invention utilizes the oxygen-containing functional groups on the surface of graphene oxide nanosheets to form a hydrogen bond effect with the hydroxyl and carbonyl groups on the polyvinyl pyrrolidone molecules, so that the polyvinyl pyrrolidone molecules are attached to the graphene oxide nanosheets. Due to the hydrophobic force of the polyvinyl pyrrolidone molecules, the zinc metal organic framework is arranged in an array on the surface of the graphene oxide to form a porous layered zinc metal organic framework. The porous layered zinc metal organic framework is carbonized by high-temperature carbonization under the protection of an inert gas to obtain a porous layered zinc oxide and carbon composite, thereby improving the UV resistance of the zinc oxide / carbon / graphene oxide. The formed carbon layer has conductivity and synergistically acts with the graphene oxide nanosheets to improve the conductive properties of the polyethylene composite film.
[0031] 3. The polyethylene composite film prepared by the present invention utilizes the adsorption properties of the porous layered structure on the surface of zinc oxide / carbon / graphene oxide to adsorb the dissolved hindered amine light stabilizer in the pores, thereby obtaining graphene oxide loaded with hindered amine light stabilizer. The porous layered structure has strong adsorption force and tension, which can firmly fix the hindered amine light stabilizer, reduce the migration of the hindered amine light stabilizer, and enable the hindered amine light stabilizer to play a synergistic role with zinc oxide to improve the ultraviolet resistance.
[0032] 4. The polyethylene composite film prepared by the present invention dopes the prepared loaded graphene oxide into the silica aerogel. The silica aerogel can improve the mechanical strength of the polyethylene film. At the same time, the silica aerogel separates the loaded graphene oxide that is easy to agglomerate, reducing the agglomeration of the loaded graphene oxide. In addition, the hydrophobically modified graphene oxide / silica aerogel has good hydrophobicity. The silica aerogel and graphene oxide can form a micron / nanostructure, further enhancing the hydrophobicity, reducing the attachment of water molecules in the air, and improving the oxidation resistance. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.
[0035] Example 1: A biaxial stretching process for a polyethylene composite film, comprising the following steps:
[0036] S1. In a reactor, 3.5 g of zinc nitrate hexahydrate was dissolved in 200 mL of DMF, and then 2 g of graphene oxide nanosheets and 3 mL of polyvinyl pyrrolidone were added, stirred and ultrasonically treated for 30 min, 4 g of 2,5-dihydroxyterephthalic acid was dissolved in 200 mL of DMF to obtain a 2,5-dihydroxyterephthalic acid DMF solution, 200 mL of the 2,5-dihydroxyterephthalic acid DMF solution was added to the reactor, stirred and mixed for 2 h, then heated to 110° C. and reacted for 1 h. After cooling, the precipitate was collected by centrifugation, washed with ethanol and deionized water, and vacuum dried at 70° C. to obtain a porous zinc skeleton / graphene oxide. The porous zinc skeleton / graphene oxide was heated to 600° C. under nitrogen protection in a tube furnace and carbonized for 2 h to obtain zinc oxide / carbon / graphene oxide.
[0037] S2. Ultrasonic dispersion of 2 g of zinc oxide / carbon / graphene oxide in 50 mL of ethanol was performed in a reactor. 1 g of HALS770 was added. After stirring and dissolving, the solvent was removed by rotary evaporation to obtain loaded graphene oxide.
[0038] S3. In a reactor, 10 g of tetraethyl orthosilicate and 80 mL of a 70 wt% ethanol aqueous solution were stirred and mixed for 8 h, the pH value was adjusted to neutral with dilute ammonia water, 3 g of loaded graphene oxide was ultrasonically dispersed in 150 mL of ethanol, added to the reactor, and ultrasonically treated for 30 min to form a gel. After aging at room temperature for 24 h, the gel was placed in a 20% volume fraction of tetraethyl orthosilicate ethanol solution for 24 h, and then the water in the gel was replaced with methanol, and the methanol in the gel was replaced with n-hexane. Finally, the gel was immersed in a mixed solution of trimethylchlorosilane and n-hexane in a volume ratio of 1:9 for 40 h to obtain a hydrophobically modified gel. The hydrophobically modified gel was dried at 50 ° C for 1 h and at 140 ° C for 2 h, and then crushed through a 300 mesh sieve to obtain graphene oxide / silica aerogel powder.
[0039] S4. 4 g of graphene oxide / silica aerogel powder and 30 g of linear low-density polyethylene were melt-blended and extruded in a twin-screw extruder at a mixing temperature of 220°C and a rotation speed of 200 rpm to obtain reinforced low-density polyethylene, and then the reinforced low-density polyethylene and 100 g of high-density polyethylene, 40 g of low-density polyethylene, 0.5 g of methyl stearate and 0.3 g of antioxidant 168 were melt-mixed and extruded into granules in a twin-screw extruder to obtain pellets at a mixing temperature of 220°C and a rotation speed of 200 rpm. The extruded pellets were compression molded into sheets at a molding temperature of 190°C, and the sheets were biaxially stretched simultaneously in two directions at 125°C at a strain rate of 3 / s to obtain a polyethylene composite film.
[0040] Example 2: A biaxial stretching process for a polyethylene composite film, comprising the following steps:
[0041] S1. In a reactor, 4.25 g of zinc nitrate hexahydrate was dissolved in 225 mL of DMF, and then 2.5 g of graphene oxide nanosheets and 3.25 mL of polyvinyl pyrrolidone were added, stirred and ultrasonically treated for 35 min, 5 g of 2,5-dihydroxyterephthalic acid was dissolved in 225 mL of DMF to obtain a 2,5-dihydroxyterephthalic acid DMF solution, 225 mL of the 2,5-dihydroxyterephthalic acid DMF solution was added to the reactor, stirred and mixed for 2.5 h, then heated to 115° C. and reacted for 1.5 h. After cooling, the precipitate was collected by centrifugation, washed with ethanol and deionized water, and vacuum dried at 75° C. to obtain a porous zinc skeleton / graphene oxide. The porous zinc skeleton / graphene oxide was heated to 650° C. under nitrogen protection in a tube furnace and carbonized for 2.5 h to obtain zinc oxide / carbon / graphene oxide.
[0042] S2. Ultrasonic dispersion of 2.5 g of zinc oxide / carbon / graphene oxide in 55 mL of ethanol was performed in a reactor. 1.5 g of HALS 770 was added. After stirring to dissolve, the solvent was removed by rotary evaporation to obtain supported graphene oxide.
[0043] S3. In a reactor, 12.5 g of tetraethyl orthosilicate and 90 mL of a 70 wt% ethanol aqueous solution were stirred and mixed for 9 h, the pH value was adjusted to neutral with dilute ammonia water, 3.5 g of loaded graphene oxide was ultrasonically dispersed in 175 mL of ethanol, added to a reactor, and ultrasonically treated for 35 min to form a gel. After aging at room temperature for 27 h, the gel was placed in a 20% volume fraction of tetraethyl orthosilicate ethanol solution for 27 h, and then the water in the gel was replaced with methanol, and the methanol in the gel was replaced with n-hexane. Finally, the gel was immersed in a mixed solution of trimethylchlorosilane and n-hexane in a volume ratio of 1:9 for 44 h to obtain a hydrophobically modified gel. The hydrophobically modified gel was dried at 55 ° C for 1.5 h and at 145 ° C for 2.5 h, and then crushed through a 300 mesh sieve to obtain graphene oxide / silica aerogel powder.
[0044] S4. 4.5 g of graphene oxide / silica aerogel powder and 35 g of linear low-density polyethylene were melt-blended and extruded in a twin-screw extruder at a mixing temperature of 232.5°C and a rotation speed of 225 rpm to obtain reinforced low-density polyethylene, and then the reinforced low-density polyethylene and 110 g of high-density polyethylene, 50 g of low-density polyethylene, 0.65 g of polyethylene wax and 0.4 g of antioxidant 1076 were melt-mixed and extruded into granules in a twin-screw extruder to obtain pellets at a mixing temperature of 232.5°C and a rotation speed of 225 rpm. The extruded pellets were compression molded into sheets at a molding temperature of 195°C, and the sheets were biaxially stretched simultaneously in two directions at 125°C at a strain rate of 3.5 / s to obtain a polyethylene composite film.
[0045] Example 3: A biaxial stretching process for a polyethylene composite film, comprising the following steps:
[0046] S1. In a reactor, 5 g of zinc nitrate hexahydrate was dissolved in 250 mL of DMF, and then 3 g of graphene oxide nanosheets and 3.5 mL of polyvinyl pyrrolidone were added, stirred and ultrasonically treated for 40 min, 6 g of 2,5-dihydroxyterephthalic acid was dissolved in 250 mL of DMF to obtain a 2,5-dihydroxyterephthalic acid DMF solution, 250 mL of the 2,5-dihydroxyterephthalic acid DMF solution was added to the reactor, stirred and mixed for 3 h, then heated to 120° C. and reacted for 2 h. After cooling, the precipitate was collected by centrifugation, washed with ethanol and deionized water, and vacuum dried at 80° C. to obtain a porous zinc skeleton / graphene oxide. The porous zinc skeleton / graphene oxide was heated to 700° C. under nitrogen protection in a tube furnace and carbonized for 3 h to obtain zinc oxide / carbon / graphene oxide.
[0047] The oxygen-containing functional groups on the surface of the graphene oxide nanosheets form hydrogen bonds with the hydroxyl and carbonyl groups on the polyvinyl pyrrolidone molecules, causing the polyvinyl pyrrolidone molecules to attach to the graphene oxide nanosheets. Due to hydrophobic forces, the polyvinyl pyrrolidone molecules are arranged in an array on the graphene oxide nanosheets. At this time, zinc ions cooperate with the pyrrole groups of the polyvinyl pyrrolidone, causing the zinc ions to be arranged on the graphene oxide nanosheets. A zinc metal organic framework is hydrothermally synthesized by the organic ligand 2,5-dihydroxyterephthalic acid and the zinc ions to obtain a porous layered zinc metal organic framework arranged in an array on the graphene oxide nanosheets. The porous layered zinc metal organic framework is carbonized by high-temperature carbonization under the protection of an inert gas to obtain a porous layered zinc oxide and carbon composite, thereby improving the UV resistance of the zinc oxide / carbon / graphene oxide. The formed carbon layer also improves the electrical conductivity.
[0048] S2. Ultrasonic dispersion of 3 g of zinc oxide / carbon / graphene oxide in 60 mL of ethanol was performed in a reactor. 2 g of HALS770 was added. After stirring and dissolving, the solvent was removed by rotary evaporation to obtain supported graphene oxide.
[0049] By utilizing the adsorption properties of the porous layered structure on the surface of zinc oxide / carbon / graphene oxide, the dissolved hindered amine light stabilizer is adsorbed in the pores to obtain graphene oxide loaded with hindered amine light stabilizer. The porous layered structure has strong adsorption and tension, which can firmly fix the hindered amine light stabilizer, reduce the migration of the hindered amine light stabilizer, and enable the hindered amine light stabilizer to work synergistically with zinc oxide to improve the UV resistance.
[0050] S3. In a reactor, 15 g of tetraethyl orthosilicate and 100 mL of a 70 wt% ethanol aqueous solution were stirred and mixed for 10 h, the pH value was adjusted to neutral with dilute ammonia water, 4 g of loaded graphene oxide was ultrasonically dispersed in 200 mL of ethanol, added to a reactor, and ultrasonically treated for 40 min to form a gel. After aging at room temperature for 30 h, the gel was placed in a 20% volume fraction of tetraethyl orthosilicate ethanol solution for 30 h, and then the water in the gel was replaced with methanol, and the methanol in the gel was replaced with n-hexane. Finally, the gel was immersed in a mixed solution of trimethylchlorosilane and n-hexane in a volume ratio of 1:9 for 48 h to obtain a hydrophobically modified gel. The hydrophobically modified gel was dried at 60 ° C for 2 h and at 150 ° C for 3 h, and then crushed through a 300 mesh sieve to obtain graphene oxide / silica aerogel powder.
[0051] The prepared loaded graphene oxide is doped into silica aerogel. Silica aerogel can improve the mechanical strength of polyethylene film. At the same time, silica aerogel separates the loaded graphene oxide that is easy to agglomerate, reducing the agglomeration of loaded graphene oxide. In addition, the hydrophobically modified graphene oxide / silica aerogel has good hydrophobic properties. Silica aerogel and graphene oxide can form a micron / nano structure, further enhancing the hydrophobic properties, reducing the attachment of water molecules in the air, and improving oxidation resistance.
[0052] S4. 5 g of graphene oxide / silica aerogel powder and 40 g of linear low-density polyethylene were melt-blended and extruded in a twin-screw extruder at a mixing temperature of 245°C and a rotation speed of 250 rpm to obtain reinforced low-density polyethylene, and then the reinforced low-density polyethylene and 120 g of high-density polyethylene, 60 g of low-density polyethylene, 0.8 g of polyethylene wax and 0.5 g of antioxidant 330 were melt-mixed and extruded into granules in a twin-screw extruder to obtain pellets at a mixing temperature of 245°C and a rotation speed of 250 rpm. The extruded pellets were compression molded into sheets at a molding temperature of 200°C, and the sheets were biaxially stretched simultaneously in two directions at 125°C at a strain rate of 4 / s in a biaxial stretcher to obtain a polyethylene composite film.
[0053] Comparative Example 1: The difference between Example 1 and S1 is that 0.8 g of nano-zinc oxide and 2 g of graphene oxide nanosheets were ultrasonically dispersed in deionized water in a reactor, 0.1 g of silane coupling agent KH550 was added, and after ultrasonic treatment for 30 min, the precipitate was collected by centrifugation and washed with deionized water to obtain zinc oxide / graphene oxide;
[0054] The porous zinc skeleton / graphene oxide is replaced by zinc oxide / graphene oxide of equal mass to obtain zinc oxide / carbon / graphene oxide, and the other steps remain unchanged to prepare a polyethylene composite film.
[0055] Comparative Example 2: The difference between Example 1 and Comparative Example 2 is that S2 is not performed. In S3, the loaded graphene oxide is replaced by an equal mass of zinc oxide / carbon / graphene oxide. In S4, 1 g of HALS 770 is added during the melt blending process of graphene oxide / silica aerogel powder and linear low-density polyethylene. The other steps remain unchanged to obtain a polyethylene composite film.
[0056] Comparative Example 3: The difference from Example 1 is that in S4, the graphene oxide / silicon dioxide aerogel powder is replaced by equal mass of nano-silicon dioxide and loaded graphene oxide, and the other steps remain unchanged to obtain a polyethylene composite film.
[0057] Graphene oxide nanosheets with a particle size of 10-15 μm and a thickness of 6-8 nm were purchased from Jiangsu Pioneer Nanotechnology Co., Ltd.
[0058] The polyethylene composite films obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were prepared into samples for performance testing. The sample thickness was 0.4 mm and the size was 30 mm × 30 mm. The tensile strength and elongation at break of the sample were tested according to the method in standard GB / T1040.2-2022. The surface resistivity of the sample was measured using a four-probe conductivity meter. After the sample was aged in an MTSGB-25 UV aging box for 200 h, the tensile strength and elongation at break of the sample were tested again.
[0059] The results are shown in Table 1:
[0060] Table 1: Performance test results
[0061]
[0062]
[0063] As can be seen from Table 1, the polyethylene composite film prepared in the present invention has good mechanical properties, and after ultraviolet irradiation aging, the tensile strength and elongation at break decrease at a low degree, indicating that it has good mechanical properties and anti-ultraviolet aging performance, and the surface resistivity is low, indicating that the antistatic performance is good.
[0064] In Comparative Example 1, nano-zinc oxide is compounded on the surface of graphene oxide nanosheets using a silane coupling agent, and zinc oxide / graphene oxide is obtained by carborundum silane coupling agent. However, zinc oxide graphene oxide does not have a porous structure, and its adsorption and binding ability for hindered amine light stabilizers is weak, and the synergistic effect of hindered amine light stabilizers and zinc oxide is reduced, resulting in easy migration of hindered amine light stabilizers and reduced anti-ultraviolet ability.
[0065] In Comparative Example 2, since the hindered amine light stabilizer is not combined with zinc oxide, its dispersion in the linear low-density polyethylene matrix is limited, and it is difficult to combine with zinc oxide, and no synergistic anti-ultraviolet oxidation effect can be produced. The anti-ultraviolet ability of the obtained polyethylene composite film is greatly reduced.
[0066] In Comparative Example 3, since nano-silica and loaded graphene oxide are not combined, the agglomeration of loaded graphene oxide cannot be reduced, and nano-silica is also easy to agglomerate, which reduces the mechanical properties of the polyethylene composite film. Due to the agglomeration of loaded graphene oxide, the surface resistance is increased and the antistatic performance is reduced.
[0067] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations can be made to the embodiments without departing from the principles and spirit of the invention.
Claims
1. A polyethylene composite film, characterized in that Calculated by mass, it contains the following components and raw materials: 4-5 parts of graphene oxide / silicon dioxide aerogel powder, 30-40 parts of linear low-density polyethylene, 100-120 parts of high-density polyethylene, 40-60 parts of low-density polyethylene, 0.5-0.8 parts of dispersant and 0.3-0.5 parts of antioxidant; The graphene oxide / silicon dioxide aerogel powder is prepared by mixing loaded graphene oxide and silicon dioxide aerogel and then subjecting them to hydrophobic modification; The loaded graphene oxide is prepared by zinc oxide / carbon / graphene oxide loaded with hindered amine light stabilizer.
2. A polyethylene composite film according to claim 1, characterized in that: The antioxidant is one of antioxidant 168, antioxidant 1076 and antioxidant 330; the dispersant is one of polyethylene wax and methyl stearate; and the hindered amine light stabilizer is HALS 770.
3. A polyethylene composite film according to claim 1, characterized in that: The graphene oxide / silicon dioxide aerogel powder is specifically prepared by the following steps: In a reactor, ethyl orthosilicate and a 70 wt% ethanol aqueous solution are stirred and mixed for 8-10 hours, and the pH value is adjusted to neutral with dilute ammonia water. The loaded graphene oxide is ultrasonically dispersed in ethanol, added to the reactor, and ultrasonically treated for 30-40 minutes to form a gel. After aging, ageing, and solvent replacement, the gel is immersed in a mixed solution of trimethylchlorosilane and n-hexane for 40-48 hours to obtain a hydrophobically modified gel. The hydrophobically modified gel is dried at 50-60° C. for 1-2 hours, and then at 140-150° C. for 2-3 hours, and then crushed through a 300-mesh sieve to obtain graphene oxide / silica aerogel powder.
4. A polyethylene composite film according to claim 3, characterized in that: The usage ratio of the ethyl orthosilicate, the ethanol aqueous solution, the loaded graphene oxide and the ethanol is 10-15 g: 80-100 mL: 3-4 g: 150-200 mL; and the volume ratio of the trimethylsilyl chloride and n-hexane is 1:
9.
5. A polyethylene composite film according to claim 4, characterized in that: The supported graphene oxide is specifically prepared by the following steps: In a reaction kettle, zinc oxide / carbon / graphene oxide is ultrasonically dispersed in ethanol, a hindered amine light stabilizer is added, and the mixture is stirred and dissolved, and then the solvent is removed by rotary evaporation to obtain loaded graphene oxide.
6. A polyethylene composite film according to claim 5, characterized in that: The usage ratio of the zinc oxide / carbon / graphene oxide, ethanol and hindered amine light stabilizer is 2-3 g:50-60 mL:1-2 g.
7. A polyethylene composite film according to claim 6, characterized in that: The zinc oxide / carbon / graphene oxide is prepared by the following steps: The porous zinc skeleton / graphene oxide was heated to 600-700° C. under nitrogen protection in a tubular furnace and carbonized for 2-3 h to obtain zinc oxide / carbon / graphene oxide.
8. A polyethylene composite film according to claim 7, characterized in that: The porous zinc skeleton / graphene oxide is prepared by the following steps: Zinc nitrate hexahydrate is dissolved in DMF in a reactor, and then graphene oxide nanosheets and 3-3.5 mL of polyvinyl pyrrolidone are added, stirred and ultrasonically treated for 30-40 minutes, and 2,5-dihydroxyterephthalic acid DMF solution is added to the reactor. After stirring and mixing for 2-3 hours, the temperature is raised to 110-120° C. and the reaction is carried out for 1-2 hours. After cooling, the precipitate is collected by centrifugation, washed with ethanol and deionized water, and vacuum dried at 70-80° C. to obtain a porous zinc skeleton / graphene oxide.
9. A polyethylene composite film according to claim 8, characterized in that: The dosage ratio of zinc nitrate hexahydrate, DMF, graphene oxide nanosheets, polyvinyl pyrrolidone and 2,5-dihydroxyterephthalic acid DMF solution is 3.5-5g:200-250mL:2-3g:200-250mL; the 2,5-dihydroxyterephthalic acid DMF solution is prepared by mixing 2,5-dihydroxyterephthalic acid and DMF according to the ratio of 4-6g:200-250mL.
10. A biaxial stretching process for a polyethylene composite film according to any one of claims 1 to 9, characterized in that: The biaxial stretching process of the polyethylene composite film comprises the following steps: Graphene oxide / silica aerogel powder and linear low-density polyethylene are melt-blended and extruded in a twin-screw extruder to obtain reinforced low-density polyethylene, and then the reinforced low-density polyethylene, high-density polyethylene, low-density polyethylene, a dispersant and an antioxidant are melt-mixed and extruded into granules in a twin-screw extruder to obtain pellets. The mixing temperature of the twin-screw extruder is 220-245°C and the rotation speed is 200-250rpm. The extruded pellets are molded into sheets at a molding temperature of 190-200°C. The sheets are simultaneously biaxially stretched in a biaxial stretcher at a strain rate of 3-4 / s and at 125-125°C to obtain a polyethylene composite film.
Citation Information
Patent Citations
Conductive packaging film, preparation method and conductive packaging bag
CN113105688A
PE film with ultraviolet shielding function and preparation method thereof
CN116589769A